2011
DOI: 10.1161/hypertensionaha.111.170266
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase 1 Is Differentially Involved in Blood Flow–Dependent Arterial Remodeling

Abstract: Abstract-Heme oxygenase 1 is induced by hemodynamic forces in vascular smooth muscle and endothelial cells. We investigated the involvement of heme oxygenase 1 in flow (shear stress)-dependent remodeling. Two or 14 days after ligation of mesenteric resistance arteries, vessels were isolated. In rats, at 14 days, diameter increased by 23% in high-flow arteries and decreased by 22% in low-flow arteries compared with normal flow vessels. Heme oxygenase activity inhibition using Tin-protoporphyrin abolished diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…HMOX1 is regarded as an antioxidative and atheroprotective gene (Pechlaner et al 2015) and has been reported to be involved in hemodynamics-related arterial remodeling (Freidja et al 2011). Although HMOX1 was up-regulated in calcific valve samples, its down-regulation in aortic valve endothelial cells under disturbed blood flow conditions may still contribute to oxidation, inflammation and calcification.…”
Section: Modulementioning
confidence: 99%
“…HMOX1 is regarded as an antioxidative and atheroprotective gene (Pechlaner et al 2015) and has been reported to be involved in hemodynamics-related arterial remodeling (Freidja et al 2011). Although HMOX1 was up-regulated in calcific valve samples, its down-regulation in aortic valve endothelial cells under disturbed blood flow conditions may still contribute to oxidation, inflammation and calcification.…”
Section: Modulementioning
confidence: 99%
“…Flowmediated outward remodeling of resistance arteries involves a transient inflammatory response (1) and oxidative stress (2) that favors the formation of peroxinitrite, which then activates metalloproteinases and extracellular matrix digestion (2,8,14,16,19). The final step, leading to diameter enlargement, requires a dilator stimulus (17). Flow-mediated outward remodeling is also associated with a compensatory increase in wall mass (11,32) due to ANG II type 1 receptor activation of ERK1/2 (11).…”
mentioning
confidence: 99%
“…MMPs induce then a partial dissociation of the extracellular matrix (ECM). In the last step, vasodilator agents, such as NO produced by eNOS (14), PGI2 produced by cyclooxygenase (COX)-2 (3), and/or carbon monoxide (CO) produced by heme oxygenase (HO)-1 (17,18), increase arterial diameter until the normalization of wall shear stress (44). In parallel, activation of the ANG II type 1 receptor (AT1R) and of MAPK ERK1/2 allow a compensatory hypertrophy aiming at normalization of wall strain induced by the diameter expansion (11).…”
mentioning
confidence: 99%
“…Furthermore, an induction of HO-1 has been reported to increase CO levels during hypertension, which can aggravate oxidative stress and promote end-organ damage. Current literature supports a relationship between hypertension, induced oxidative stress and an activation in the heme oxygenase system (Botros et al 2007, Freidja et al 2011. Also, AngII induction of HO-1 leads to an increase in endogenous CO levels (Aizawa et al 2000, Li et al 2004, Quadri et al 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Also, AngII induction of HO-1 leads to an increase in endogenous CO levels (Aizawa et al 2000, Li et al 2004, Quadri et al 2014). Therefore, the adverse effects of significant increases in endogenously formed CO levels could be mediated through an induction of the oxidative stress pathway and/or reduction in NO which has been reported to increase superoxide formation and could be associated with endorgan damage (Jadhav et al 2008, Freidja et al 2011). Thus, the regulation of vascular tone by CO appears to be concentration dependent, where substantial elevations of CO levels via an increase in HO activity, produces an inhibition of NOS and contributes to endothelial dysfunction in several models of hypertension (Ndisang et al 2002, Teran et al 2005).…”
Section: Introductionmentioning
confidence: 99%